Pengembangan Media Pembelajaran Sejarah Berbasis Komik Di Kelas XI IPS 1 SMA Negeri 10 Kota Jambi - Nurhayati, Aurora Nandya Febriyanti (Universitas Batanghari Jambi, 2018)
Abstract This study aims to develop media to discuss the history of Vostenigde Oostindische Compagnie or VOC in Indonesia in Class XI IPS 1 of SMA Negeri 10 Jambi City. This research uses research and development methods. The subjects of the study were students of class XI IPS 1 of SMA Negeri 10 Jambi City in semester I. Data collection was carried out using questionnaires, interviews, and interviews. The research instrument uses content validity. Data analysis techniques using descriptive quantitative and qualitative. The comic media developed during the development of ADDIE are grouped into five stages, Analysis (analysis), Design (design), Development (Development), Implementation (Implementation), and Evaluation (Evaluation). Media writing that is developed qualitatively and qualitatively deserves to be applied in learning. In general, each material and media expert were 8.38 for material experts and (curriculum suitability, correctness of content and presentation of material including very good) and 8.47 (production, visual design, and technical quality) including very good list). Meanwhile, which provides students at the pilot stage, wider trials, and operational try respectively 10.70 (including very good criteria); 14.29 (including very good); and 14.84 (including very good criteria). Qualitatively, the comic media